Forming the Linguistic and Social-Cultural Competence of Students Who Learn Several Foreign Languages at Home-Reading Classes of the Language-Focused Higher Schools - Nataliia Andriichuk (Pedagogical Discourse, 2014)
The article brings up the question of prospective improvement of general methodological principles which regulate the teaching of a first foreign language. The author suggests to use the inner resources of the first foreign language so as to ease the students’ way into acquiring a basic command of the social-cultural parameters of a second foreign language. Suggested is a complex of exercises to be used in home-reading classes aimed at forming the linguistic and social-cultural competence of junior language school students and, in particular, at making them acquainted with the stereotyped British vision of other European cultures and the nationally conditioned features of their representatives.